2013
DOI: 10.1016/j.neurobiolaging.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vesicular monoamine transporter 2 polymorphisms in Parkinson’s disease

Abstract: Generation of reactive oxygen species during dopamine (DA) oxidation could be one of the factors leading to the selective loss of nigral dopaminergic neurons in Parkinson’s disease (PD). Vesicular monoamine transporter type 2 (VMAT2) proteins in nerve terminals uptake dopamine into synaptic vesicles, preventing its cytoplasmic accumulation and toxic damage to nigral neurons. Polymorphisms in VMAT2 gene and in its regulatory regions might therefore serve as genetic risk factors for PD. In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 25 publications
1
50
2
Order By: Relevance
“…Previous studies modeling Parkinson disease in Drosophila demonstrated that overexpression of the vesicular monoamine transporter promotes packaging of dopamine into vesicles, thereby lowering its cytoplasmic concentrations (19,39). Human genetic studies have found that single nucleotide polymorphisms (SNPs) within the promoter region of VMAT2, in particular gain-of-function haplotypes, are also associated with decreased risk of PD in women (40). Furthermore, in mice, reduced VMAT2 function produces dopamine-mediated toxicity and neurodegeneration in the nigrostriatal dopamine system, and restoration of VMAT2 function may be an important intervention in the treatment of PD (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies modeling Parkinson disease in Drosophila demonstrated that overexpression of the vesicular monoamine transporter promotes packaging of dopamine into vesicles, thereby lowering its cytoplasmic concentrations (19,39). Human genetic studies have found that single nucleotide polymorphisms (SNPs) within the promoter region of VMAT2, in particular gain-of-function haplotypes, are also associated with decreased risk of PD in women (40). Furthermore, in mice, reduced VMAT2 function produces dopamine-mediated toxicity and neurodegeneration in the nigrostriatal dopamine system, and restoration of VMAT2 function may be an important intervention in the treatment of PD (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…disease (29,30). Although the detrimental effects of reduced VMAT2 function are recognized, our understanding of the potential benefits of increased VMAT2 function in vivo has been limited to a Drosophila model (31)(32)(33).…”
mentioning
confidence: 99%
“…The top five up and down-regulated DEGs were shown in the Table 1. Among these genes, solute carrier family 18 (SLC18A2), expressed in central, peripheral, and enteric neurons as well as in platelets [20], is capable of uptaking dopamine into intracellular secretory vesicles, preventing its toxicity in the cytosol and discharging it into the extracellular space by exocytosis [21]. Study has showed that SLC18A2 messenger RNA (mRNA) levels were reduced in platelets from PD patients [22].…”
Section: Differentially Expressed Genes Analysis Between Pd and Healtmentioning
confidence: 99%